The effectiveness of mindfulness-based cognitive therapy on cognitive regulation of emotion and perceived stress in women with dental anxiety - Seyedi, Vajieh Alsadat; Meghdadi, Maryam (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to determine the effectiveness of mindfulness-based cognitive therapy on cognitive regulation of emotion and perceived stress in women with dental anxiety. Method: The research method is semi-experimental pre-test and post-test with a control group. The study population included all women with dental anxiety in Tehran who were selected by available sampling method and randomly assigned to two groups (15 people) experimental group and (15 people) control group. The experimental group underwent 8 sessions of 90 minutes of cognitive therapy based on the mindfulness of Segal et al. (2004). The research instruments were Stouthard, Mellenbergh, & Hoogstraten (1993) Dental Anxiety Questionnaire, Garnefski, Kraaij, & Spinhoven (2001) Cognitive Emotion Regulation, and Cohen et al. (1983) Perceived Stress. The results were analyzed using repeated measures analysis of variance and SPSS.22 software. Results: It showed that mindfulness-based cognitive therapy treatment had a significant effect on increasing cognitive regulation of emotion (F=51.53, P